E-Learning: Factors Affecting Online Training For Multimedia Super Corridor (MSC) Companies In Malaysia - Yea, Chang Hou (2002)
The concern on E-Learning training concept for companies is important. Hence, the study that is focusing on companies especially Multimedia Super Corridor (MSC) Status company is been carried out. This study seeks to examine the factors affecting the online training/E-learning program for MSC Status company.